Algebra for every eighth grade student: one size fits all? - Best, Lori (My University, 2011)
The purpose of this paper is to investigate the reasons why Minnesota enacted legislation in 2007 requiring the enrollment in and successful completion of algebra 1 by every eighth grade student, and how, specifically, one school district implemented changes to meet this requirement. From the "new math" of the 1960's to standards-based reform of the 21st century, United States public school students have been subjected to various trends in education; yet when compared to other countries, standardized test scores have fallen. How can this trend be reversed? The U.S. federal government has imposed legislation to require all students to demonstrate proficiency as measured on annual high-stakes testing. Each state has been challenged to increase the rigor in math as public schools across the country are working to meet the ever-increasing proficiency targets laid out in No Child Left Behind. Algebra 1 content, in both the Minnesota academic standards and the Common Core math standards, is expected to be mastered by students at an earlier age than ever before. How can students achieve this goal? In this paper you will learn how the administration and math department at the middle school in Hastings, Minnesota, began increasing the rigor for students with new curriculum and teacher staff development. They recognized the success of a program dedicated to the lowest scoring 8th grade math students. This required a change in the math scheduling model and allocated fifty percent more time for students in math class. Teachers used the time for more instruction, one-on-one guidance, hands-on activities, technology exploration, and discovery lessons. The results, as measured by the state's annual assessment, showed a noticeable increase in proficiency for Hastings eighth graders while the overall state average decreased from the previous year. These results and scheduling model may be helpful to districts interested in increasing student proficiency rates.
Plan B Paper. 2011. Master of Science in Education-Secondary Mathematics--University of Wisconsin-River Falls. Math Department. 49 leaves. Includes bibliographical references (leaves 24-26).
Keywords: Algebra; Eighth grade students; Algebra--Study and teaching--Standards--Minnesota; Curriculum development; Mathematics; Algebra--Study and teaching (Middle school)